Comparison of maternal and umbilical cord blood HIF-1α and nitric oxide levels in early and late onset preeclamptic pregnancies. (2nd December 2015) - Demircan Sezer, Selda; Küçük, Mert; Nergiz Avcıoğlu, Sümeyra; Zafer, Emre; Altınkaya, Sunduz Özlem; Bıçakçı, Burcu; Yenisey, Çiğdem; Yüksel, Hasan; Kurt Ömürlü, İmran
Abstract: Objective : Despite the absence of a complete physiologic–pathologic understanding, common accepted theory for development of preeclampsia is incomplete trophoblastic invasion leading to failed uterine and spiral arteriolar remodeling, causing maternal vascular endothelial dysfunction by secreted molecules in response to decreased placental perfusion, placental hypoxia, and ischemia. Placental angiogenesis is especially ineffective in early onset preeclampsia and fetal morbidity/mortality rates are higher because of further decreased blood flow. In this study, we aim to compare the maternal and umbilical cord blood levels of hypoxia-inducible transcription factor-1α (HIF-1α), which is believed to regulate hypoxia-related transcriptional responses, to play role in activating genes for initial phases of placental development and angiogenesis and a physiologic vasodilator molecule nitric oxide (NO) in normal, early and late onset preeclamptic pregnant women. Methods : Pregnant women who were diagnosed with preeclampsia (early onset ≤34 weeks; late onset >34 weeks) and delivered in our clinic were enrolled for this prospective case-controlled study. Pregnant women without preeclampsia were recruited as control group. HIF-1α and NO levels in maternal and umbilical cord blood measured and compared among groups. Findings : A total of 46 cases were enrolled for this study, including 25 preeclamptic (13 in the early onset group and 12 in the late onset group) and 21 normal pregnant women in the control group. Comparison of preeclampsia group to controls revealed higher maternal blood HIF-1α levels in the control group, however higher umbilical cord NO levels in the preeclampsia group ( p  < 0.05 and p  < 0.001, respectively). In a second analysis, when compared to control group, both early and late onset preeclampsia subgroups were found to have higher umbilical cord blood NO levels ( p  < 0.001). Results : In this study, we observed lower maternal blood HIF-1α levels and higher umbilical cord NO levels in preeclampsia group than controls. These findings suggest that umbilical cord blood NO levels in pregnant women with preeclampsia increase in response to hypoxia. However, lower HIF-1α levels in preeclampsia group can be due to our limited number of cases and we think that there is a need for further studies with larger sample size.